Limitation of runaway electron beam duration in air-filled gap with inhomogeneous field; Technical Physics Letters; Vol. 37, № 4 - Yalandin M. I.; Mesyats G. A. Gennady Andreyevich; Reutova A. G.; Sharypov K. A.; Shpak V. G.; Shunailov S. A. (2011, 2011)
В фонде НТБ ТПУ отсутствует